Nilai-nilai Pendidikan Islam dalam Puisi Qum li al-Mu‘allimi Waffihi al-Tabjīlā Karya Ahmed Shawky: Kajian Semiotika Charles Sanders Peirce: Islamic Educational Values in Ahmed Shawky’s Poem Qum li al-Mu‘allimi Waffihi al-Tabjīlā: A Semiotic Study of Charles Sanders Peirce - Ridho Hidayat; Fadlil Yani Ainusyamsi; Rohanda Rohanda; Isma Fauziah (Madrasah Tsanawiyah DDI Cilellang, 2024)
Literary works are often considered mere entertainment. In fact, these works can be used as educational messages, especially related to the phenomenon of transformation—tending towards decadence―of students' morals and characters amidst changing times. Educational values have shifted. Inappropriate attitudes towards teachers in the past have become commonplace today for various academic and theoretical reasons. These values are reflected in the poem Qum li al-Mu‘allimi Waffihi al-Tabjīlā by Ahmed Shawky. This poem emphasizes the importance of respect for teachers as symbols of wisdom and sources of knowledge. This research aims to reveal the meaning of Islamic education values in the poem through Charles Sanders Peirce's semiotic approach. The main focus of the research is the idea of Islamic education, and the poem is the material object. This research uses a descriptive qualitative method with a semiotic analysis of the three main elements in Peirce’s theory: icons, indexes, and symbols. This analysis is used to interpret the representation of the values of faith, worship, and morals in the poem. The results show that the values of Islamic education in this poem are knowledge is an important part of faith; respecting teachers is part of worship, even the law is obligatory as obligatory as worshiping Allah; and learning must be based on good ethics. This study implies that respect for teachers is more important than knowledge itself. Because noble morals are a sign of the blessing of knowledge and student success.